Textual scholarship and the making of the New Testament - Parker, David C. (Oxford University Press, 2013)
The book is going through its biggest revolution since Gutenberg. Thanks to computer tools and electronic publication the concept and realisation of critical editions are being rethought. David C. Parker looks at how new methodology changes what an edition is for and how we use it, using the example of the New Testament texts